Memorizing Short Letters to Strengthen the Kinaesthetic Learning Style of Elementary School Students - Aulia Ramadhani Mahmud; Sutama Sutama (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2026)
Memorizing short surahs forms students' religious character. The religious characters formed include discipline, self-confidence, and honesty. The purpose of this study is 1) To describe the habit of memorizing Makkiyah surahs to strengthen the kinaesthetic learning style. 2) To explore the habit of memorizing Madaniyyah surahs to strengthen the kinaesthetic learning style. This type of research is qualitative-phenomenological. The research subjects were the principal, Islamic Religious Education teachers, and third-grade students at the elementary school where the research was conducted. Data were collected through interviews, observations, and documents. Data validity was verified by triangulation of sources and methods. Data were analyzed inductively. The results of the study: 1) The habit of memorizing Makkiyah surahs to strengthen the kinaesthetic learning style was carried out by tapping the table, raising hands, and playing relay games. Through these three movements, students' kinaesthetic learning style can be strengthened, namely by focusing on memorization. 2) The habit of memorizing Madaniyyah letters to strengthen the kinaesthetic learning style, carried out by pointing upwards, sideways, and marching in place. Through the teacher's body movements, students' kinaesthetic learning style becomes more active, and they are confident in memorizing letters.